Design for Aging: Perspectives on Technology, Older Adults, and Educating Engineers - Caitrin Lynch (Anthropology & Aging, 2015)
Does the development of new technologies invariably contribute positively to the daily lives of older adults in the contemporary United States and elsewhere? Eleven years into teaching anthropology to engineers, and five years into co-teaching a course on design for aging called “Engineering for Humanity,” my answer is: Not always, but we can make it so.